Molecular Detection and Genotyping of Velogenic Newcastle Disease Virus in Broiler Chickens Using PCR and Sequencing (Indian Journal of Animal Production and Management, 2025)
Newcastle disease (ND) is caused by a virulent strain of paramyxovirus type 1  (APMV-1) infected with high morbidity and mortality, ND consider highly  pathogenic disease of poultry and is caused by virulent, messogenic and lentogenic  strains of Newcastle disease virus (NDV). The velogenic NDV infected poultry  and cause high mortality high economic loses in poultry industry. In last year’s  Broilers and layer poultry farms in Iraq suffer from high morbidity and mortality,  clinically characterized by tortocalus with greenish diarrhea and sharp decrease  in egg production with high morbidity and mortality, grossly characterized by  ulceration in proventriculus, cecal tonsils and payer’s patches, so that this research  was designed for identification of velogenic strains of NDV in Iraq. Fifteen samples  (trachea, spleen and intestine) were collected from infected poultry flock after (3-5)  days post clinical signs appear. The molecular methods (RT-PCR) test confirmed  three samples infected with vNDV, Nucleotide sequences of vNDV were obtained  from NCBI websites and alignment with other researchers concerned in this topic.  The three sequencing results in this study have been submitted to the gene bank  database under accession number MN901943.1, MN901944.1, and MN901945.1,  phylogenetic analysis of our sequences were used to relatedness of strain obtaining  with other vNDV around the world, the a current sequences of NDV strains were  found to be related as a common ancestor with Iranian registered NDV.
Keywords: Newcastle disease (ND); RT-PCR; degenerate primer; phylogenetic tree